2021
DOI: 10.2147/jir.s318327
|View full text |Cite
|
Sign up to set email alerts
|

Role of Goblet Cells in Intestinal Barrier and Mucosal Immunity

Abstract: Goblet cells and the mucus they secrete serve as an important barrier, preventing pathogens from invading the mucosa to cause intestinal inflammation. The perspective regarding goblet cells and mucus has changed, with current evidence suggesting that they are not passive but play a positive role in maintaining intestinal tract immunity and mucosal homeostasis. Goblet cells could obtain luminal antigens, presenting them to the underlying antigen-presenting cells (APCs) that induces adaptive immune responses. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(93 citation statements)
references
References 123 publications
(184 reference statements)
2
89
0
2
Order By: Relevance
“…In the present study, we also observed that EA administrations alleviated microvilli shedding and crypt hyperplasia, as well as increased the number of goblet cells in piglets injected with PQ, which is consistent with previous studies [ 51 ]. Oxidative stress can cause the intestinal barrier injury mainly manifested as villi shorting, crypt hyperplasia, and goblet cells apoptosis, which contribute further to a reduced ability for nutritional absorption and presentation of pathogens [ 62 , 63 ]. Maintaining intestinal integrity is a prerequisite to ensure the intestinal barrier function [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also observed that EA administrations alleviated microvilli shedding and crypt hyperplasia, as well as increased the number of goblet cells in piglets injected with PQ, which is consistent with previous studies [ 51 ]. Oxidative stress can cause the intestinal barrier injury mainly manifested as villi shorting, crypt hyperplasia, and goblet cells apoptosis, which contribute further to a reduced ability for nutritional absorption and presentation of pathogens [ 62 , 63 ]. Maintaining intestinal integrity is a prerequisite to ensure the intestinal barrier function [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being continually exposed to bacteria and parasites, mucus produced by the gut epithelium needs to be constantly renewed and recompositioned. This process stays under strict immune control (reviewed elsewhere [ 53 , 54 ]), however, regulation by Trefoil Factor Family proteins (TFFs) is worth mentioning due to the direct cooperation with another regulator of the immune response—amphiregulin—which is released in response to IL-33 by group 2 innate lymphoid cells (ILC2s) and protects tissue from damage [ 55 ] and facilitates worm expulsion [ 56 ]. Firstly, TFF3 enhances rheological mucus properties, improving barrier stability.…”
Section: Mucus As the First Physical Frontiermentioning
confidence: 99%
“…This could be attributed to the high turnover of epithelial cells in the colon, requiring a constant need for goblet cell differentiation and maturation, especially upon inflammation-induced tissue damage. The differentiation of goblet cells is controlled by a Notch-dependent pathway, and the terminal differentiation involves KrĂŒppel-like transcription factor 4 (KLF4), growth factor independence 1 (GFI1) and SAM pointed domain-containing ETS transcription factor (SPDEF) [ 116 , 117 ]. Hath1, a basic helix–loop–helix transcription factor, is needed to counter the differentiation towards absorptive cell development [ 118 ].…”
Section: Permeability Of the Gut Epithelial Barriermentioning
confidence: 99%